"Companion, friend, four-legged fluff ball": The power of pets in the lives of LGBTQ+ young people experiencing homelessness. (September 2022) - Schmitz, Rachel M; Carlisle, Zachary T; Tabler, Jennifer
Experiences of homelessness are challenging for lesbian, gay, bisexual, transgender, and/or queer (LGBTQ+) young people. LGBTQ+ young adults without stable housing endure mental health struggles stemming from multiple structural disadvantages. In navigating stressors, LGBTQ+ young people may develop bonds with companion animals, or pets. Demonstrating the diverse ways LGBTQ+ young adults manage mental health challenges while homeless, we qualitatively analyzed the narratives of 17 LGBTQ+ young adults (18–25) surrounding their pet relationships. Participants emphasized the positive power of pets in their lives to help offset stressors. These findings illustrate how marginalized young people manage their mental health through informal resources. Incorporating companion animals could potentially enhance services for LGBTQ+ youth experiencing marginalization.